Russia : the challenges of transformation - Dutkiewicz, Piotr; Trenin, Dmitriĭ (Possible futures series, 2011)
In Russia a group of leading Russian intellectuals and social scientists join with top researchers from the world to examine the social, political, and economic transformation of Russia. This timely and important book of original essays makes clear that neither politics nor economics alone holds the key to Russia's future, presenting critical perspectives on challenges facing Russia, both in its domestic policies and in its international relations. It also explores how global order - or disorder - may develop over the coming decades.